Formulation of Investigation of Criminal Acts of Theft with Justice-Based Aggravation (Case Study of Nabire Police Resort) - Anugerah, Muhammad Dito; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
Indonesia is a unitary state in the form of a republic. This statement is clearly stated in Article 1 Paragraph 3 of the Fourth Amendment to the 1945 Constitution of the Republic of Indonesia, which states that Indonesia is a country of law. Based on the supremacy of law, it states that "Indonesia is a country that upholds human dignity in relation to laws and regulations, and the government must enforce the law without exception. The type of research used in this study is normative legal research. Normative legal research is research that aims to analyze and examine law as a norm or rule that applies in society. The focus of this research is legal materials, either in the form of laws and regulations, doctrines, legal principles, or relevant court decisions. 1. The current mechanism for investigating aggravated theft is carried out based on the provisions of the Criminal Procedure Code (KUHAP), starting from the reporting stage, investigation, inquiry, to the transfer of the case to the prosecution stage. 2. Weaknesses in aggravated theft investigations include the limited ability of investigators to comprehensively uncover initial evidence, minimal use of supporting technology, and lack of sensitivity to the perpetrator's social background. 3. The legal formulation of the investigation of the crime of theft with aggravation based on justice should be directed at integrating the values of Pancasila justice, especially the second and fifth principles.